1999
DOI: 10.1074/jbc.274.47.33807
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Caldesmon Is Required for Binding to the Shc·Grb2 Complex

Abstract: S3-v-erbB isTogether, these studies demonstrate that the major sites of tyrosine phosphorylation on CaD are located in the myosin and actin binding domains of CaD and that Tyr-27 is the major tyrosine phosphorylation site through which CaD interacts with the Shc⅐Grb2 complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…These results were confirmed and extended using site-directed mutants of caldesmon, which individually lack each of the three previously characterized phosphotyrosine acceptor sites of caldesmon (i.e. tyrosines 27, 165, and 363) (Wang et al, 1999). Figure 5 illustrates that only phosphotyrosine-27 of caldesmon is required for binding to either the aminoterminal SH3 or central SH2 domains of Grb2.…”
Section: Grb2 Interacts With Caldesmon Through the Aminoterminal Sh3 supporting
confidence: 61%
See 2 more Smart Citations
“…These results were confirmed and extended using site-directed mutants of caldesmon, which individually lack each of the three previously characterized phosphotyrosine acceptor sites of caldesmon (i.e. tyrosines 27, 165, and 363) (Wang et al, 1999). Figure 5 illustrates that only phosphotyrosine-27 of caldesmon is required for binding to either the aminoterminal SH3 or central SH2 domains of Grb2.…”
Section: Grb2 Interacts With Caldesmon Through the Aminoterminal Sh3 supporting
confidence: 61%
“…We have previously shown that transformation by S3-vErbB involves the tyrosine phosphorylation of several novel cytoplasmic targets, and is not simply the amplification of well-characterized mitogenic signaling events (McManus et al, 1995Wang et al, 1999;Boerner et al, 2000Boerner et al, , 2001. In this report, we demonstrate that Grb2 plays a central role in modulating the integrity of the actin-based cytoskeleton during ligand-independent S3-v-ErbB-mediated transformation.…”
Section: Grb2 and Caldesmon Interactions In Transformed Fibroblastsmentioning
confidence: 50%
See 1 more Smart Citation
“…It is clear that the phosphotyrosine protein complex in vErbB-transformed fibroblasts contains several components that potentially can regulate the actomyosin-based cytoskeleton. One such regulatory protein is the tyrosine-phosphorylated form of caldesmon, which is a stable component of a Shc-Grb2 signal adapter complex in v-ErbB-transformed fibroblasts (21). To determine if this Shc-Grb2-caldesmon phosphoprotein complex is a stable subunit of an even larger multiprotein module involving Nck and Pak, we looked for a caldesmon-Pak interaction by co-precipitation assay.…”
Section: Formation Of a Transformation-specific Signaling Complex In mentioning
confidence: 99%
“…In addition, two cytoskeletal associated proteins, i.e. caldesmon and p21-activated kinase, are uniquely tyrosine-phosphorylated in S3v-ErbB-transformed cells (2,4,38). Interestingly, Ras activation, a key aspect of ligand-dependent EGFR mitogenic signaling, is not required for S3v-ErbB-mediated transformation or for these cytoskeletal changes (5).…”
mentioning
confidence: 99%